2009
DOI: 10.1088/0004-637x/708/1/26
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Nebular Continuum and Line Emission in Observations of Young Massive Star Clusters

Abstract: In this spectroscopic study of infant massive star clusters, we find that continuum emission from ionized gas rivals the stellar luminosity at optical wavelengths. In addition, we find that nebular line emission is significant in many commonly used broadband Hubble Space Telescope (HST) filters including the F814W I-band, the F555W V-band, and the F435W B-band. Two young massive clusters (YMCs) in the nearby starburst galaxy NGC 4449 were targeted for follow-up spectroscopic observations after Reines et al. di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
130
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(142 citation statements)
references
References 32 publications
12
130
0
Order By: Relevance
“…The position of many of them below the theoretical line is consistent with internal reddening shifting their colors to redder values consistent with the dusty clouds in which they are born. Reines et al (2010) show that nebular emission can significantly affect magnitudes and colors of young massive star clusters (<5 Myr). Figure 6 shows the spatial distribution of these very young clusters on a Galex FUV image.…”
Section: Color-color Diagramsmentioning
confidence: 95%
“…The position of many of them below the theoretical line is consistent with internal reddening shifting their colors to redder values consistent with the dusty clouds in which they are born. Reines et al (2010) show that nebular emission can significantly affect magnitudes and colors of young massive star clusters (<5 Myr). Figure 6 shows the spatial distribution of these very young clusters on a Galex FUV image.…”
Section: Color-color Diagramsmentioning
confidence: 95%
“…We do not include attenuation for the AGN SED, although we include it statistically as an obscured fraction, an approach that Ricci et al (2017b) showed to produce a good match between UV and X-ray AGN LFs. We do not include emission lines either, which can boost both the AGN (Vanden Berk et al 2001;Hainline et al 2011) and the galaxy magnitude (Reines et al 2010;Atek et al 2011;Stark et al 2013;de Barros et al 2014). Nebular emission will be studied in a companion paper.…”
Section: Agn Spectramentioning
confidence: 99%
“…This is caused by the contribution of neighbouring sources as well as the nebular emission from nearby (often related) ionised gas which is stronger at redder wavelengths (e.g., Reines et al 2010;Adamo et al 2010a). Models that include nebular emission can explain some of this excess near-IR emission, however, for some clusters the models cannot account for the additional flux.…”
Section: Discussionmentioning
confidence: 99%
“…Part of the excess comes from the nebular emission 2 from the ionised gas around the clusters (Reines et al 2010, Adamo et al 2010a, which begins to significantly contribute to the integrated flux of the cluster from the I-band red-ward. However, even when taking the nebular emission into account, a number of clusters show near-IR excess that increases with increasing wavelength (e..g, Adamo et al 2010a).…”
Section: Introductionmentioning
confidence: 99%